Survey of the labour market for information specialists in Lithuania - Elena Maceviciute (Information Research: An International Electronic Journal)
This paper reports on the results of surveys carried out in Lithuania and Estonia in 1995 and 1996, the main aim of which was to provide a basis for planning the development of information management courses in the Baltic States. In the course of the project it was necessary to resolve certain methodological difficulties in the identification of the concept 'information specialist' and in the process of data collection. The results show the recruitment rates needed over the next three years and the qualities and skills needed by information specialists.